2006
DOI: 10.1104/pp.105.074971
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Stimulates a Calcium-Dependent Protein Kinase in Grape Berry

Abstract: It has been demonstrated that calcium plays a central role in mediating abscisic acid (ABA) signaling, but many of the Ca 21 -binding sensory proteins as the components of the ABA-signaling pathway remain to be elucidated. Here we identified, characterized, and purified a 58-kD ABA-stimulated calcium-dependent protein kinase from the mesocarp of grape berries (Vitis vinifera 3 Vitis labrusca), designated ACPK1 (for ABA-stimulated calcium-dependent protein kinase1). ABA stimulates ACPK1 in a dose-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 112 publications
(110 reference statements)
0
66
0
1
Order By: Relevance
“…ABA treatment of grape cells led to the regulation of many genes known to be ABA and stress related. For instance, genes specifically affected by the ABA treatment encode (1) proteins involved in osmotic stress, desiccation (raffinose synthase and LEA), and biotic stress (PR protein) responses, (2) proteins known to improve stress tolerance to abiotic stresses (AP2-DREB, bZIP, and NAC), and (3) members of ABA signaling (PP2C) and calcium signaling (calmodulin and calmodulin-stimulated protein kinase; Desikan et al, 2001;Yu et al, 2006;Nishimura et al, 2007;Nakashima et al, 2009;Park et al, 2009;Wang et al, 2011; Table II). Our results confirm data from the literature and validate these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA treatment of grape cells led to the regulation of many genes known to be ABA and stress related. For instance, genes specifically affected by the ABA treatment encode (1) proteins involved in osmotic stress, desiccation (raffinose synthase and LEA), and biotic stress (PR protein) responses, (2) proteins known to improve stress tolerance to abiotic stresses (AP2-DREB, bZIP, and NAC), and (3) members of ABA signaling (PP2C) and calcium signaling (calmodulin and calmodulin-stimulated protein kinase; Desikan et al, 2001;Yu et al, 2006;Nishimura et al, 2007;Nakashima et al, 2009;Park et al, 2009;Wang et al, 2011; Table II). Our results confirm data from the literature and validate these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…ABA content of grape berries gradually and strongly increases just before the onset of ripening, called véraison (Coombe and Hale, 1973;Scienza et al, 1978;Davies et al, 1997;Antolín et al, 2003;Deluc et al, 2009). In relation with its accumulation profile, numerous reports suggested that ABA may play a major role in controlling several ripening-associated processes of grape berry, including coloration, sugar accumulation, and softening (Coombe, 1992;Davies et al, 1997;Giovannoni, 2001; Rodrigo et al, 2003;Yu et al, 2006;Wheeler et al, 2009;Gambetta et al, 2010;Giribaldi et al, 2010;Gagné et al, 2011).…”
mentioning
confidence: 99%
“…The expression of two grape Suc transporters, VvSUT1 and VvSUC12, and two hexose transporters, VvHT1 and VvHT2, was shown to be up-regulated in berries from the onset of ripening (Davies et al, 1999;Fillion et al, 1999;Ageorges et al, 2000;Manning et al, 2001;Vignault et al, 2005), which potentially provides machinery to mediate this trans-membrane transport pathway of soluble sugars. Plasma membrane H 1 -ATPase, which drives sugar transporters by generating the proton motive force across plasma membranes (Sondergaard et al, 2004), was shown to be activated by an abscisic acid-stimulated protein kinase that was up-regulated from the onset of ripening (Yu et al, 2006), supporting the occurrence of an enhanced capability of trans-membrane sugar transport from this time. The young growing grape berries during Stages I and II accumulate a level of soluble sugars comparable to or even lower than that in the phloem of pedicel (see Fig.…”
Section: Possible Mechanism and Significance Of The Shift Of Phloem Umentioning
confidence: 97%
“…The protein kinase responsible for this phosphorylation has not yet been identified. Recently, it was reported that calcium-dependent protein kinase (CDPK) stimulated by abscisic acid leads to phosphorylation-dependent activation of H + -ATPase (Yu et al, 2006). In rice, a 55 kDa calcium-dependent protein kinase was shown to phosphorylate two Thr residues from the autoregulatory domain (region I) of the plasma membrane proton pump (Ookura et al, 2005).…”
Section: Regulation By Phosphorylationmentioning
confidence: 99%